"The desert's no home for a rose": Filipinx childhood and music as aesthetic experience. Issue 2 (June 2021) - Mecija, Casey
This article examines Diane Paragas' film Yellow Rose (2019) for its capacity to offer important insights into the reparative utility of music for a child separated from a parent due to deportation. While the film depicts the brutality of contemporary U.S. migration policies, Yellow Rose is also a story about the role of aesthetic expression in childhood's diasporic imaginaries. The film teaches us about the agentic potential of music as a mode of dealing with the trauma of forced separation. In particular, the genre of American country music is affectively instrumentalized by the film's young, Filipinx protagonist. In deepening my argument, I work with the film to explain that the kinship between Rose and a genre of music that is hegemonically associated with whiteness produces a "queer sonic" that serves as conduit for the emergence of contingent networks of care and methods of survival. I propose that queer sonic expression, or the unassimilable qualities of sound and genre, is a site where we can broaden racialized imaginings of Filipinx childhood, as it offers an opportunity for reparation.